Comparison of National and International Legal Frameworks on Nickel Export Ban and Its Environmental Impact - Delyarahmi, Sucy; Oktaviandra, Surya; Faizka, Muhammad; Amalia, Nazwa (Faculty of Law, Andalas University, 2024)
Indonesia's regulation of a ban on nickel exports at <1.7% (less than one point seven percent) has caused international upheaval. Reactions emerged from European Union countries that viewed Indonesia as having violated GATT 1994. In this research, the authors use the normative method with a comparative approach and literature study. The results showed that Indonesia's nickel export ban policy aligns with the government's efforts to improve the downstream industry. However, this policy has a negative impact on the environment, including increased water pollution due to nickel industry waste that exceeds the quality standards regulated in environmental regulations. This is due to the massive nickel exploitation that is not in line with the original purpose of the export ban to maintain domestic nickel stocks.